Easy French reader a three-part text for beginning students - De Roussy de Sales, R. (Richard) (New York McGraw-Hill, 2015)
An easy-to-follow guide to French that includes engaging readings in both English and French to help build comprehension and confidence in using the language.
"Expand your word through language."--Cover.
Keywords: French language -- Readers